Managing stories about quality. (4th August 2014) - Midgley, Gerald; Kadiri, Yah'ya; Vahl, Martha
This paper explores issues of information flow between organisations and their clients using a case study of a Social Services Department in the North of England. The purpose of the study was to make recommendations for improving public access to services through the effective use of information. The Department's usual practice of producing and distributing leaflets and brochures was looked at as part of a wider information system, which included the stories that circulate in the community about service quality. It was discovered that people use these stories to interpret what is presented to them in the form of leaflets and brochures. If they hear negative stories about quality, they tend to disregard leaflets, perceiving them as irrelevant, and do not access services. The issues of quality and access are therefore intimately linked through such stones. In consequence, as part of an information strategy, it was recommended that the Social Services Department should undertake a new initiative to improve service quality, defining quality in terms of the stories people tell about their contacts with services. In such an initiative, an important task is to make sure that the staff and clients of the organisation are supported in developing stories that both facilitate access to services and also 'force' services to be improved. The paper ends with some reflections on the common assumption that it is useful to distinguish between formal and informal information in seeking to improve information management. It is argued that this assumption should be treated with caution: when there is a wish to intervene in, rather than simply observe, information systems, the distinction between formal and informal information rapidly becomes redundant. An alternative way of conceptualising the improvement of information systems is proposed.